EVALUATION OF DIFFERENT SYNTHETIC AND BOTANICAL INSECTICIDE AGAINST APHID, APHIS GOSSYPII GLOVER INFESTING ISABGOL CROP - S. J. PATIL,; B. R. PATEL, (The Bioscan, 2013)
An investigation was carried out during 2008-09 to evaluate the different insecticides against aphid, Aphis gossypii Glover infesting isabgol (Plantago ovata) crop under field condition at Sardarkrushinagar, S. D. A. U., Dantiwada. The result of the field study revealed that, among all the chemical and botanical insecticides used, carbosulfan @ 0.05 per cent was found to be most effective by recording lowest population of aphid as per aphid indexing method (0.99 A. I.) with the highest seed yield, 11.24 q/ha and neem oil @ 0.5 per cent was superior than other botanical recording (1.83 A. I.) with a maximum 7.21 q/ha seed yield. Thus, from the overall results it can be concluded that the carbosulfan @ 0.05 and neem oil 0.5 per cent proved most effective for the management of aphid A. gossypii in isabgol crop.